Kitsune fox: messenger, protector, trickster, and seductive - Muñoz Fernández, Irene M. (Estudios Complutenses de Asia Oriental, 2025)
The Kitsune fox is a well-known figure in connection with the cult of Inari. The relationship between Inari and foxes has not always been clear-cut: not all deities somehow linked to rice, agriculture, cereals, or food are accompanied by a fox, nor are all fox deities associated with Inari. Furthermore, the image of Kitsune will evolve into that of a supernatural trickster being. This work aims to analyze the origins of the connection between Kitsune and Inari, as well as the magical nature of foxes in Ancient Japan, encompassing both their agriculture-related attributes and their mysterious-trickster aspects.